Peculiarities of capacity characteristics of n -TіO2/p-CdTe heterostructures, obtained by spray- pirolise method - Брус, Віктор Васильович; Ілащук, Марія Іванівна; Парфенюк, Орест Архипович; Мар’янчук, Павло Дмитрович; Гавалешко, Наталія Миколаївна (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of electrical properties of anisotype heterojunctions ТіО2/p-CdTe, prepared by TiO2 thin film deposition onto freshly cleaved CdTe single crystal substrates using the spray pyrolysis technique, was carried out. The determined height of the potential barrier of the heterojunction under investigation еφк are equal to 1.36 and 2.94 eV at T=295 K and T=0 K. Since the electrical junction is formed in CdTe (Eg=1,5 еV), the obtained values of еφк were explained by the formation of a thin high-resistance layer on the semiconductor’s surface as well as by the presence of surface states at the heterojunction interface. The established features of the C-V characteristics well correlate with the mentioned assumptions